PTU-179 Diagnostic Yield of Eus-Fna in Pancreatic Neuro-Endocrine Tumours (PNET) – Solid Versus Cystic Pnets – 9 Year Experience from a Tertiary Centre. (4th June 2013) - Mitra, V; Nayar, M; Leeds, J; Haugk, B; Wadehra, V; Charnley, R; Jaques, B; White, S; Manas, D; French, J; Oppong, K
Abstract : Introduction: The detection and diagnosis of pNETs remains challenging. EUS and EUS-FNA has a significant role in the detection, precise localisation and cytological confirmation of pNETs. Methods: A retrospective review of all pNET patients undergoing EUS-FNA between April 2003 and September 2011 was carried out to determine the efficacy of EUS-FNA in confirming pNETs and compare performance over two consecutive 4 year period. Results: 10 patients (3% of EUS procedures for cystic lesions) with cystic pNETs and 44 (4% of EUS procedures for solid lesions) with solid pNETs were identified. Table 1 compares the size, demographics and diagnostic performance of radiology, EUS & cytology in solid and cystic pNETs. 17 and 5 solid and cystic pNETs respectively were diagnosed between 2003 and 2007 while 27 and 5 solid and cystic pNETs were diagnosed between 2008 and 2011. EUS-FNA diagnosis of cystic and solid pNETs has improved from 20% and 59% respectively between 2003 and 2007 to 100% and 81% respectively between 2008 and 2011. Overall, sensitivity of EUS cytology has improved from 50% to 84.4% (p = 0.015) during this period. Malignant potential of solid pNETs was higher (54.5% vs 20%) compared to cystic pNETs. Curative resection was higher in patients with cystic pNETs (80% vs 68%) compared to solid pNETs. Conclusion: EUS & EUS-FNA is a useful test in diagnosing pNETs. Overall, the sensitivity of combined EUS imaging and cytology was significantly better compared to CT/MRI (p < 0.05) in detecting pNETs across all groups. Sensitivity of combined EUS imaging and cytology was significantly better compared to EUS imaging alone (p < 0.05) in the solid and combined pNET cohort of patients. Sensitivity of EUS cytology was significantly better compared to EUS imaging (p < 0.05) in the solid and combined pNET cohort of patients. Comparing the first 4 years to the second, there has been an increase in the number of cases of pNETs and statistically significant improvement in the diagnostic performance of cytology. Disclosure of Interest: None Declared.